Pengabdian Sebagai Dewan Juri Lomba Kompetensi Siswa (LKS) Bidang Web Technologies SMK Tingkat Provinsi Kalimantan Utara - Muntiari, Novita Ranti; Haryansyah (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
The Student Competency Competition is an annual competition between students at vocational school level according to the areas of expertise taught at the participating vocational schools. This worksheet is equivalent to the OSN (National Science Olympiad) which is held in middle/high school. This activity is one part of a series of selections to get the best students from all over Indonesia who will be further guided by their respective competition field teams and will be included in international level skill competencies. The aim of the community service activities carried out through this LKS competition is for the Court Team to contribute as a jury in the competition Web Technologies. The role of the jury is as the center for determining the provincial level LKS competition, so that the results of the selection of the best students will represent North Kalimantan Province to enter the competition at the national level. The final result of this community service activity is a decision from the council regarding the competition assessment process in determining the winner of the LKS competition at the North Kalimantan Province level.